2022
DOI: 10.3390/ma15176006
|View full text |Cite
|
Sign up to set email alerts
|

Direct Writing of Functional Layer by Selective Laser Sintering of Nanoparticles for Emerging Applications: A Review

Abstract: Selective laser sintering of nanoparticles enables the direct and rapid formation of a functional layer even on heat-sensitive flexible and stretchable substrates, and is rising as a pioneering fabrication technology for future-oriented applications. To date, laser sintering has been successfully applied to various target nanomaterials including a wide range of metal and metal-oxide nanoparticles, and extensive investigation of relevant experimental schemes have not only reduced the minimum feature size but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 144 publications
0
2
0
Order By: Relevance
“…Selective laser sintering is a representative direct writing method. 97 Luo et al 98 reported a facile and scalable direct laser writing (DLW)-assisted technique for generating porous carbon platelets (PCPs) with uniform size and arbitrarily designed shapes. This innovative approach leverages CO 2 laser irradiation to induce carbonization of a biomass composite sheet.…”
Section: Porous Carbon Derived From Powder Bed Fusionmentioning
confidence: 99%
“…Selective laser sintering is a representative direct writing method. 97 Luo et al 98 reported a facile and scalable direct laser writing (DLW)-assisted technique for generating porous carbon platelets (PCPs) with uniform size and arbitrarily designed shapes. This innovative approach leverages CO 2 laser irradiation to induce carbonization of a biomass composite sheet.…”
Section: Porous Carbon Derived From Powder Bed Fusionmentioning
confidence: 99%
“…The laser process has the advantage of selective processing, low thermal damage to the substrate, and applicability to complex conformal structures. Moreover, a laser can be faster and more conveniently applicable to various substrates than a furnace, which can help optimize conventional methods. Laser pyrolysis of organic polymers (polysilazane/polydimethylsiloxane) has been applied to fabricate multiple ceramic coatings, , sophisticated polydimethylsiloxane microstructures, and flexible sensors. Laser reductive sintering has been demonstrated to fabricate highly sensitive temperature sensors .…”
Section: Introductionmentioning
confidence: 99%